The gender dimension of social change : the contribution of dynamic research to the study of women's life courses / edited by Elisabetta Ruspini and Angela Dale. - Ruspini, Elisabetta; Dale, Angela, 1945- (Policy Press, 2002)
This new study uses longitudinal data to provide new insights into the changing dynamics of lives of women today. In particular, it explores the potential of longitudinal or life course analysis as a powerful tool for appreciating the gender dimension of social life.